MOHS micrographic surgery for treating erosive adenoma of the nipple: a case report and review of the literature. (27th September 2017) - Barco, Israel; Vidal, MCarmen; Fraile, Manel; Masferrer, Emili; Barco, Leo; Barco, Didac; Baez, Cinthya J.; Giménez, Nuria; Pessarrodona, Antoni; García‐Fernández, Antonio
Abstract: Background: Erosive adenoma of the nipple (EAN) is a benign condition that involves major ducts of the nipple. Its clinical presentation may resemble other disorders. Complete removal of the nipple is often suggested because of frequent relapse. However, adverse cosmetic and functional results have prompted clinicians to look for other more conservative options. Aims: To present a case of EAN successfully treated using Mohs micrographic surgery (MMS) and summarize differential diagnosis and treatment. Materials and Methods: A 40‐year‐old woman with EAN was diagnosed by immunohistochemical markers after clinical suspicion. We have reviewed other cases treated with MMS in the literature. Results: In this patient, lesion size was 0.8 cm and the margin specimen was 1 × 0.9 × 0.2 cm, with EAN as histopathologic diagnosis. No atypia or malignancy was reported. Final esthetic outcome was reached with only one session, under local anesthesia and on an outpatient basis. Discussion: Dermatologic lesions appearing on the nipple's surface should be closely followed. Paget's disease, carcinoma or proliferative lesions like EAN have to be considered, and such conditions require different surgical approaches. Traditional complete removal of the nipple is performed in many cases, but it may result in over‐treatment and unfavorable cosmetic outcome. MMS is frequently used in dermatologic surgery to treat malignant lesions with a high cure rate, avoiding excess tissue excision and leading to better patient satisfaction. Conclusion: EAN can be successfully treated by minimal resection, especially if early diagnosis is done. MMS offers a better aesthetic outcome than traditional total excision.